Western waters: New Mexico's Big Ditch and groundwater in Colorado's South Platte Valley - Kryloff, Nicolai Alexander, author; Orsi, Jared, 1970-, advisor; Fiege, Mark, advisor; Ward, Robert C., committee member (Colorado State University. Libraries, 2008)
Water is at the heart of history in the American West. This connection ought to be especially lucid to westerners, but in fact the opposite is often true. Water seems to pour out of our faucets by magic – its origins hidden, its journey obscure. Environmental history can help reclaim the lost relationships between people and this vital substance which shapes western landscapes, livelihoods, and lives. The main goal of the essays herein is to contribute to this understanding. This thesis consists of two distinct but related historical threads, both dealing with western water. The advantage of writing two separate, concise pieces of historical analysis for this volume is their added flexibility as publishable items. To achieve the shorter lengths necessary for this approach, extensive historiographical research was condensed in the final articles, though much of it is still evident in the footnotes and bibliography of each essay. An additional benefit derived from two short articles is an expanded temporal, topical, and geographical scope. Western water is a vast subject, and many important stories remain untold. In this pair of essays, I have attempted to recover some fragments of this forgotten past.
Department Head: Doug Yarrington.